2008
DOI: 10.1038/jcbfm.2008.150
|View full text |Cite
|
Sign up to set email alerts
|

Cell Fusion Contributes to Pericyte Formation after Stroke

Abstract: Recent reports have shown that bone marrow-derived cells (BMDCs) contribute to the formation of vasculature after stroke. However, the mechanism by which mural cells are formed from BMDC remains elusive. Here, we provide direct evidence that the cell fusion process contributes to the formation of pericytes after stroke. We generated mouse bone marrow chimeras using a cre/lox system that allows the detection of fusion events by X-gal staining. In these mice, we detected X-gal-positive cells that expressed vimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
1
20
1
1
Order By: Relevance
“…Remarkably, pericytes were not only detected on nearby BBB, but also at the probe/tissue interface for all WT and caspase-1 KO tissue. In the adult CNS of mice, PDGFRβ is expressed in pericytes [110], and blood-borne bone marrow progenitor cells have been shown to contribute to CNS pericytes following ischemic injury [111113]. Pericytes have many additional roles associated with the BBB such as secreting essential extracellular matrix proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, pericytes were not only detected on nearby BBB, but also at the probe/tissue interface for all WT and caspase-1 KO tissue. In the adult CNS of mice, PDGFRβ is expressed in pericytes [110], and blood-borne bone marrow progenitor cells have been shown to contribute to CNS pericytes following ischemic injury [111113]. Pericytes have many additional roles associated with the BBB such as secreting essential extracellular matrix proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In stroke mouse models, fused cells of bone marrowderived cell expressing specific markers for mature pericyte increased in the ischemic areas. These results indicated that pericytes were formed by cell fusion and the process participated in angiogenesis following stroke (Piquer-Gil et al 2009). Adult bone marrow is considered to be a rich reservoir of pericyte progenitor cells.…”
Section: Origin Of Pericytesmentioning
confidence: 94%
“…Whether this process continues during vascular remodeling in the adult and aging CNS has yet to be experimentally proven. More recently, circulating mesoderm-derived bone marrow progeni- tor cells have been shown to contribute to adult CNS pericyte pools after ischemia 2931 . The relative contributions of circulating pericyte progenitor cells and local, preexisting CNS pericyte pools to renewal of pericytes in the adult CNS under normal conditions and after CNS acute and chronic injury remain to be determined.…”
Section: Origin Of Cns Pericytesmentioning
confidence: 99%